The Impact of Strategic Planning Practices on Quality Improvement in Christian Higher Education Institutions - Simanjuntak, Junihot M.; Usmanij, Perus A. (Badan Litbang dan Diklat Kementerian Agama RI, 2024)
Quality development particularly through strategic planning is essential to meet market demands. However, its role as a strategic resource in Christian Religious Higher Education Institutions remains unexplored in determining program implementation. This study examines the quality improvement of Christian Religious Higher Education in Indonesia through strategic planning. Employing a qualitative descriptive approach, data were collected from interviews and literature studies, including journals and related documents. Data are then analyzed using Creswell’s method. The findings indicate that these institutions require: 1) effective leadership training programs to develop and regularly review strategic plans, which include identifying core values, defining missions based on surrounding needs, assessing strengths and weaknesses, and formulating action plans through earnest prayer to achieve desired goals; and 2) expertise and skills in implementing higher education management strategies to diagnose, plan, design, and systematically compile documents, establish policies, motivate faculty and staff, allocate human resources, and develop a strategic culture that supports institutional and program quality improvement. Challenges in strategic planning include improper formulation and a lack of strong organizational leadership support. The study concludes that strategic planning encompassing quality training, process improvement, benchmarking, open culture, employee empowerment, and executive commitment can enable.